The Use of Energy Resources as Foreign Policy Tools: The Russian Case - A.Sait Sonmez; Sedat Cobanoglu (European Scientific Journal, ESJ, 2016)
The energy industry has an important place in the policies of Vladimir Putin, who became the president of Russia in 2000. During this period, Russia’s economic and political power has increased through the rise of oil prices. Accordingly, Russia began to follow pro-active foreign policy on a global scale. “Energy Resources” used as a tool in foreign policy, are one of the dimensions of this proactive policy. In this study, how the energy resources are used in foreign policies of states is analyzed by the sample of Russia. Furthermore, the place of energy industry in the Russian economy and some of the outstanding companies operating in this industry are examined. On the other hand transportation policies (the energy corridors of Russia), performed inside and outside the country, are accompanied with some examples. Then, the role of energy is analyzed in the outputs of foreign policy followed by Russia.